Artificial Thermostable D-Amino Acid Dehydrogenase: Creation and Application - Akita, Hironaga; Hayashi, Junji; Sakuraba, Haruhiko; Ohshima, Toshihisa (Frontiers in Microbiology, 2018)
Many kinds of NAD(P)-dependent L-amino acid dehydrogenases have been so far found and effectively used for synthesis of L-amino acids and their analogs, and for their sensing. By contrast, similar biotechnological use of D-amino acid dehydrogenase (D-AADH) has not been achieved because useful D-AADH has not been found from natural resources. Recently, using protein engineering methods, an NADP+-dependent D-amino acid dehydrogenase (D-AADH) was created from meso-diaminopimelate dehydrogenase (meso-DAPDH). The artificially created D-AADH catalyzed the reversible NADP+-dependent oxidative deamination of D-amino acids to 2-oxo acids. The enzyme, especially thermostable one from thermophiles, was efficiently applicable to synthesis of D-branched-chain amino acids (D-BCAAs), with high yields and optical purity, and was useful for the practical synthesis of 13C- and/or 15N-labeled D-BCAAs. The enzyme also made it possible to assay D-isoleucine selectively in a mixture of isoleucine isomers. Analyses of the three-dimensional structures of meso-DAPDH and D-AADH, and designed mutations based on the information obtained made it possible to markedly enhance enzyme activity and to create D-AADH homologs with desired reactivity profiles. The methods described here may be an effective approach to artificial creation of biotechnologically useful enzymes.